Synthesis of Tricyclic Lactams from Heterocyclic Imines - Stalling, Timo; Martens, Jürgen (Synthesis, 2013)
Starting from different heterocyclic imines, a large number of annulated tricyclic lactams were prepared in a two-step synthesis. First, methoxyamides with a phenyl ring in α- or β-position were generated. Finally, these substrates were converted to valero- and caprolactams, respectively, via intramolecular Friedel–Crafts cyclization in the presence of a Lewis acid. Additionally, effects of substituent groups at the phenyl ring in the electrophilic aromatic substitution were investigated.
Keywords: heterocycles; imines; amides; lactams; cyclization; electrophilic aromatic substitution